Agrarian landscapes in transition : comparisons of long-term ecological and cultural change - Redman, Charles L.; Foster, David R., 1954- (Long-Term Ecological Research Network series., 2008)
Agrarian Landscapes in Transition researches human interaction with the earth. With hundreds of acres of agricultural land going out of production every day, the introduction, spread, and abandonment of agriculture represents the most pervasive alteration of the Earth's environment for several thousand years. What happens when humans impose their spatial and temporal signatures on ecological regimes, and how does this manipulation affect the earth and nature's desire for equilibrium?. Studies were conducted at six Long Term Ecological Research sites within the US, including New England, the Ap.